Beneficial effects of Foeniculum vulgare on ethanol-induced acute gastric mucosal injury in rats - Birdane, Fatih Mehmet (Baishideng Publishing Group Co., Limited, 2007)
AIM: To examine the anti-ulcerogenic and antioxidant effects of aqueous extracts of Foeniculum vulgare (FVE) on ethanol-induced gastric lesions in rats. METHODS: FVE was administered by gavage at doses of 75, 150 and 300 mg/kg, and famotidine was used at the dose of 20 mg/kg. Following a 60 min period, all the rats were given 1 mL of ethanol (80%) by gavage. One hour after the administration of ethanol, all groups were sacrificed, and the gastric ulcer index was calculated; whole blood malondialdehyde (MDA) and reduced glutathione (GSH), serum nitrate, nitrite, ascorbic acid, retinol and β-carotene levels were measured in all the groups. RESULTS: It was found that pretreatment with FVE significantly reduced ethanol-induced gastric damage. This effect of FVE was highest and statistically significant in 300 mg/kg group compared with the control (4.18 ± 2.81 vs 13.15 ± 4.08, P < 0.001). Also, pretreatment with FVE significantly reduced the MDA levels, while significantly increased GSH, nitrite, nitrate, ascorbic acid, retinol and β-carotene levels. CONCLUSION: FVE has clearly a protective effect against ethanol-induced gastric mucosal lesion, and this effect, at least in part, depends upon the reduction in lipid peroxidation and augmentation in the antioxidant activity.